The Effect of Employee Competency and Organizational Commitment on Personnel Performance in the Community Development Unit of the Bekasi City Metro Resort Police - Puji Astuti; Yuni Pratikno; Jamal Hanaffy (Dinasti Publisher, 2026)
Personnel performance is a crucial factor in supporting the improvement of performance and professionalism of police officers, especially in the Community Development Unit of the Bekasi City Metro Police Resort which has a strategic role in fostering and providing services to the community. Optimal personnel performance is influenced by various internal organizational factors, including employee competence and organizational commitment. This study aims to analyze the influence of employee competence and organizational commitment on personnel performance, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 89 personnel of the Community Development Unit of the Bekasi City Metro Police Resort as respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPSS version 29 program. The results of the study indicate that partially employee competence has a positive and significant effect on personnel performance, with a t-value of 4.510 and a significance level of <0.001. Organizational commitment also has a positive and significant effect on personnel performance, with a t-value of 4.639 and a significance level of <0.001. Simultaneously, employee competence and organizational commitment have a significant effect on personnel performance, as indicated by the F-value of 23.577 with a significance level of <0.001. The coefficient of determination (R Square) of 0.354 indicates that employee competence and organizational commitment are able to explain 35.4% of the variation in personnel performance, while the remaining 64.6% is influenced by other factors outside the research model. This finding confirms that increasing employee competence accompanied by strengthening organizational commitment on an ongoing basis plays an important role in improving personnel performance at the Community Development Unit of the Bekasi City Metro Police Resort